Dostoevsky and English modernism, 1900-1930 - Kaye, Peter, 1952- (Cambridge University Press, 2004)
This book examines how seven major English novelists - D.H. Lawrence, Virginia Woolf, Arnold Bennett, Joseph Conrad, E.M. Forster, Henry James, and John Galsworthy - responded to the work of the Russian writer Fyodor Dostoevsky in the early years of the twentieth century.